1997
DOI: 10.1038/sj.bmt.1700717
|View full text |Cite
|
Sign up to set email alerts
|

Long-term engraftment failure after marrow ablation and autologous hematopoietic reconstitution: differences between peripheral blood stem cell and bone marrow recipients

Abstract: Summary:Since early studies demonstrated the feasibility of hematopoietic reconstitution by infusion of peripheral blood stem cells (PBSC), 1-4 autologous PBSC transplantation has We infused peripheral blood stem cells (PBSC) into 51 patients with various malignant disorders, after myebecome an established procedure in clinical oncology. In many centers, including our own, the majority of autololoablative conditioning. Twenty-four patients also received autologous bone marrow (PBSC + BM). In a gous transplanta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
13
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 2 publications
2
13
2
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] However, variables that influence hematopoiesis function long term after transplantation have not been analyzed sufficiently.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[4][5][6][7][8][9][10][11][12][13][14][15][16] However, variables that influence hematopoiesis function long term after transplantation have not been analyzed sufficiently.…”
Section: Discussionmentioning
confidence: 99%
“…recovery are: number of prior chemotherapeutic regimens and age 12 -both with a negative effect -and source of progenitor cells. 6,12 Clinical studies have shown that mobilized peripheral blood (PB) stem cells as compared to bone marrow (BM) cells are associated with earlier hematological recovery and reduced usage of blood components during the post-transplant period.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] Similarly, low yields of CD34 + cells and hematopoietic progenitor/stem cells during peripheral blood mobilization regimens correlated with the type and timing of prior chemotherapy. [9][10][11] The causes for these deficiencies have not been ascertained.…”
mentioning
confidence: 99%